The heterogeneous and regressive consequences of COVID-19: evidence from high quality panel data - Low, H; Crossley, T; Fisher, P (University of Oxford, 2020)
Using new data from the Understanding Society COVID-19 Study collected in two waves in April and in May 2020 in the UK, we make three contributions. First, Understanding Society is based on probability samples and the Covid-19 Study is carefully constructed to support valid population inferences. Second, the panel allows a long-run measure of income to characterise regressivity. Third, we have novel data on the mitigation strategies that households use. Our key findings are that those with precarious employment, under 30 and from minority ethnic groups face the biggest labour market shocks. Almost 50% of individuals have experienced declines in household earnings of at least 10%, but declines are most severe in the bottom income quintiles. Methods of mitigation vary substantially across groups: borrowing and transfers from family and friends are most prevalent among those most in need.